"Toxic atmosphere effect": Uncivil online comments cue negative audience perceptions of news outlet credibility. (January 2023) - Masullo, Gina M; Tenenboim, Ori; Lu, Shuning
Uncivil user comments have been found to have a negative effect on how people perceive an issue featured in the news, a news story, or a journalist who reports a news story. To advance this line of research, we draw on expectancy violations theory and the concept of heuristic cues to theorize the toxic atmosphere effect . We theorize that incivility in online comment threads could pose an even larger challenge to news organizations by cuing news audience members to perceive an entire news outlet—not just an individual story—as lacking in credibility. Based on two experiments in the United States (Study 1, n = 520; Study 2, n = 1056), we show that exposure to incivility can lead people to perceive a news outlet as less credible even though the incivility did not directly attack the news outlet. Such effects hold true even when people are exposed to comment threads in which the first several comments are civil. Democratic and business implications are discussed.